Is unplanned out-of-hospital birth managed by paramedics 'infrequent', 'normal' and 'uncomplicated'? - Belinda Flanagan; Bill Lord; Margaret Barnes (BMC, 2017)
Abstract Background Unplanned out-of-hospital birth is often perceived as precipitate in nature, 'infrequent', 'normal' and 'uncomplicated'. However, international studies report unplanned out-of-hospital birth is associated with increased rates of maternal and neonatal morbidity and mortality. This research describes intrapartum, immediate postpartum and neonatal care provided by paramedics in Queensland, Australia. The objectives were to (1) determine the number of cases where the paramedic documented birth or imminent birth during the study period (2) to describe the incidence of births prior to or during paramedic care (3) to detail any risk factors and/or complications recorded by paramedics during these cases, (4) identify paramedic pain management practices for intrapartum care, and (5) to examine the maternal and neonatal outcomes as documented by paramedics. Method A retrospective analysis of Queensland Ambulance Service (QAS) de-identified patient care records, generated from clinical case data between the 1st of Jan 2010 and 31st of Dec 2011, was undertaken. Descriptive analysis and x 2 tests were used to test associations between categorical variables, and the Wilcoxon rank-sum for associates between continuous variables which were not normally distributed. Content analysis was utilised to code free text fields. Results Six thousand one hundred thirty-five records were identified as intrapartum cases. This represented approximately 0.5% of the annual QAS caseload; 5722 were classified as maternal records and 413 were neonatal records. Paramedics recorded antenatal and/or intrapartum complications in 27.3% (n = 1563) of cases. Abnormal maternal vital signs were recorded in 30.1% (n = 1725) of cases. Of the 5722 women attended by paramedics during their labour, a birth occured in 10.8% (n = 618) of cases. Parity was documented in 41.4% (n = 256) of mothers who birthed. Neonatal records were available for 66.8% (n = 413) of actual births, 60.0% (n = 248) recorded a full set of neonatal vital signs and an Apgar score. When an Apgar score was recorded, 21.8% (n = 91) scored ≤7 out of 10. Conclusions The research described intrapartum, immediate postpartum and neonatal care provided by paramedics and identified factors that may complicate paramedic clinical management of labouring and birthing women. Further research is required to determine if there are opportunities to improve the paramedic management of such cases.